Investigating Estate Surveyors and Valuers' Awareness and Application of Arbitration in Resolving Real Estate Disputes in Akure, Nigeria - Akinlabi, A. J. (International Journal of Real Estate, 2025)
The study investigates the use of arbitration in resolving real estate disputes among estate surveying and valuation firms in Akure, Nigeria. A survey was conducted with 26 firms, revealing that 65% do not utilise arbitration regularly. Rent collection and payment were identified as major contentious issues. Factors influencing arbitration preference included enforceability, predictability, finality, confidentiality, and cost-effectiveness. Limitations included sampling bias and reliance on self-reported data. The study highlights the importance of promoting awareness, training, and support for arbitration in estate management practices. It emphasises the social implications of fostering a culture of arbitration for enhancing efficiency and integrity in Nigeria's real estate sector. The findings contribute to the literature by shedding light on arbitration utilisation and factors influencing its preference in real estate dispute resolution. The study underscores the need to address barriers to arbitration adoption and promote it as a viable alternative for resolving real estate disputes effectively.
Keywords: Arbitration; Real Estate Disputes; Estate Surveying and Valuation; Dispute Resolution; Akure; Nigeria